Analysis of the Implementation ff Academic Supervision in Elementary Schools : A Case Study of Public and Private Elementary School - Kristiyani, Margareta; Karsono, Karsono; Roemintoyo, Roemintoyo (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
Improving the calibre of teaching and learning in elementary education and raising teacher professionalism depend critically on academic supervision. Still, its actual application is usually administrative and hasn't worked effectively as a tool for professional development. This study examines the contextual variables that affect these practices as well as compares how public and private elementary schools apply academic monitoring. Qualitative technique using a comparative case study design gathered data by means of interviews, observations, and documents including school supervisors, instructors, and principals. Strict bureaucratic demands suggest that in public schools supervision is typically formalistic and geared toward administrative compliance, which reduces its influence on teacher growth. By contrast, private schools usually use more flexible, interactive, and ongoing supervisory techniques. In conclusion, the study emphasizes the need of a contextual, cooperative, and reflective supervisory strategy to successfully support teacher growth and improve learning quality